Identification and Functional Characterization of Short Linear Motifs (SLiMs) in “Core” RxLR effector proteins from Phytophthora parasitica var nicotianae - Moleleki, Lucy N. (University of Pretoria, 2022)
Thesis (PhD (Microbiology))--University of Pretoria, 2022.